2018
DOI: 10.1001/jamanetworkopen.2018.4087
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Time-Series Machine Learning Methods for Forecasting Hospital Discharge Volume

Abstract: Key PointsQuestionWhat is the performance of a new time-series machine learning method for predicting hospital discharge volume?FindingsIn this cohort study of daily hospital discharge volumes at 2 academic medical centers (101 867 patient discharges), predictors of discharge volume were well calibrated. These findings were achieved even with shorter training sets and infrequent retraining.MeaningThese results appear to demonstrate the feasibility of deploying simple time-series methods to more precisely estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Furthermore, some models that have predicted daily discharges have done so across all patients in the hospital, which is potentially useful at the hospital level but not actionable for clinical teams caring for the individual patient. 18,19 Limitations Our study has some limitations. The model was trained and validated on patients within a single institution; thus, its generalizability to other hospitals is uncertain.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, some models that have predicted daily discharges have done so across all patients in the hospital, which is potentially useful at the hospital level but not actionable for clinical teams caring for the individual patient. 18,19 Limitations Our study has some limitations. The model was trained and validated on patients within a single institution; thus, its generalizability to other hospitals is uncertain.…”
Section: Discussionmentioning
confidence: 94%
“…Scope Predicted outcome Methodology Tabak et al (2014) All inpatients Mortality Linear regression Van Walraven and Forster (2017) All inpatients Discharge volume Survival analysis McCoy et al (2018) Hospital level Discharge volume Time series Rajkomar et al (2018) All inpatients Mortality, overall LOS > 7 days Deep learning Safavi et al (2019) Surgical inpatients Remaining LOS < 1 day Deep learning most severe patients. Patients who cannot be admitted to an ICU due to congestion have to be admitted to a general care bed, leading to increased length of stay and readmission risk (Kim et al 2016).…”
Section: Referencementioning
confidence: 99%
“…Recently, Van Walraven and Forster (2017) use non-parametric models to predict the daily number of hospital discharges with accuracy roughly comparable to ours (median relative error: 1.4%; IQR −5.5% to 7.1%). McCoy et al (2018) forecasted discharge volume in two hospitals using time-series algorithm with a mean absolute error of 11.5 and 11.7 beds respectively ( R 2 = 0.843 and 0.726 respectively).…”
Section: Predictive Accuracy On Retrospective Datamentioning
confidence: 99%
See 1 more Smart Citation
“…16 17 This has motivated operationsfocused researchers to develop automated predictions of individual discharges or discharge volume using data available in the electronic health record (EHR). [17][18][19][20] These retrospective analyses have demonstrated that EHR-data-driven models can perform as well-and sometimes better-than clinician-driven predictions. 17 However, to our knowledge, there have been limited published studies demonstrating translation of an automated discharge prediction model into clinical practice with analysis of impact on operational outcomes.…”
Section: Introductionmentioning
confidence: 99%